Strategi Pembelajaran Aktif untuk Meningkatkan Pemahaman Materi Kuliah Antar Semester - Muhammad Zuhdi; Joni Rokhmat (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2021)
Active Learning Strategies to Improve Understanding of Fundamental Physics Objects. Physics is one of the subjects considered difficult by students. The learning strategies applied by the teacher must be well structured in order to be able to provide understanding to students. Active learning strategies need to be done to improve understanding of physics properly and correctly. This study was conducted to determine the effectiveness of active learning to improve understanding of physics in prospective teachers. This active learning strategy is combined with causalitics and cognitive conflict learning methods which are applied to inter-semester course material at the end of the 2018 – 2019 school year. Learning with this combination of methods is able to provide a good understanding of existing students. The post-test results, which were compared with the pre-test results, showed an increase in the average student understanding of up to 24%. Active learning is proven to be able to improve the understanding of lecture material for students.  Keywords: active learning, physics education